RELEVANSI DAN POLA PROGRAM INTERNSHIP KE JEPANG BERDASARKAN PERSEPSI MAHASISWA - Suyanti Suyanti; Dwi Nita Aryani (POLITEKNIK LP3I JAKARTA, 2026)
The internship program in Japan is one of the strategic efforts to enhance students’ competencies through international work experience. This study aims to analyze the relevance and implementation patterns of the Japan internship program based on the perceptions of participated students at STIE Malangkucecwara. This research employs a qualitative descriptive approach using a survey method, with data collected through questionnaires distributed to 22 students who have participated in the internship program. The results indicate that the Japan internship program has a relatively high level of relevance in supporting students’ competency development, particularly in terms of soft skills, such as work-related skills, cultural adaptability, and communication in an international environment. Companies generally provide training, facilities, and job guidance. On the other hand, students still face several challenges, particularly in terms of Japanese language proficiency and socio-cultural adaptation in the workplace. Nevertheless, students are able to adapt through direct experience and support from the work environment. Therefore, the Japan internship program plays an important role in enhancing students’ work readiness and global competitiveness. It is recommended that improvements be made in language preparation, cultural understanding, and alignment between academic fields and job placements to increase the effectiveness of the internship program.